Economic outlook of rice crops in Pakistan: a time series analysis (1970–2015) - Abdul Rehman; Luan Jingdong; Abbas Ali Chandio; Muhammad Shabbir; Imran Hussain (Financial Innovation, 2017)
Background: The basic objective of this study was to examine the relationship between the rice output, its production area, water availability, and agricultural gross domestic product (GDP) of Pakistan. Annual time series data for 1970-2015 were collected from the National Food Security and Research, Economic Survey of Pakistan, and Pakistan Bureau of Statistics (various publications). Methods: Rice crop data were analyzed using the ordinary least square method and the augmented Dickey-Fuller test. Were interpreted using the Johansen cointegration test. Results: Our study revealed the existence of a long-standing relationship between rice output, its production area, and water availability with the agricultural GDP of Pakistan. Regression results indicate that rice output and cultivated area have a significant and positive relationship with agricultural GDP, while water availability has a negative relationship. Conclusions: The study suggests that the government of Pakistan should design new policies and funding schemes for developing and improving water availability.
Keywords: 650; Rice output; Water availability; Agricultural GDP; OLS methods; Aromatic basmati Rice; irrigation system